Opinions of Psychiatrists and Emergency Medicine Physicians on the Crime of Healthcare Professionals Not Reporting the Crime Regarding Violence Against Women: Situation Assessment and Evaluations - Yılmaz Karaman, İmran Gökçen and Oktar, Seyhan and Köse, Cansu and Çanakçı, Mustafa Emin and Taşkın, Ozan Ercan (The Bulletin of Legal Medicine, 2024)
Objective: Article 280 of the Turkish Penal Code (TPC) concerns healthcare professionals reporting crimes. Psychiatrists and emergency physicians who frequently encounter patients who have been exposed to violence against women (VAW) are faced with a dilemma when the patient does not want judicial notification. Methods: 138 psychiatrists and 70 emergency medicine physicians participated in the research. In the online survey, participants were asked about their level of knowledge, their attitudes towards VAW, and their experiences with VAW cases. Trends in making judicial notifications and keeping medical records were examined based on physical violence (PV) and sexual violence (SV) case reports. Results: Regarding the case examples, physicians’ tendencies to keep medical records and make judicial notifications differ for PV and SV. Emergency medicine physicians are more likely to make judicial notifications in VAW cases than psychiatrists (each p<0.001). The tendency to make a judicial report and to make a medical record) was higher in the PV case than in the SV case. Being a specialist physician increased the probability of reporting PV by 2.1 times (p=0.009). All psychiatrists and 91% of emergency physicians are concerned about the physical safety of their patients in case reports. Conclusion: In its current state, the crime of a healthcare professional not reporting the crime leaves physicians in a dilemma between doing what is suitable for the patient’s well-being and doing what is legal. The relevant law needs to be reviewed, and physicians should be trained on the forensic aspects of VAW cases.